Pemberdayaan Warga Masyarakat Desa Gonilan Melalui Pelatihan Akupresur Pada Kasus Hiperkolesterol - Kurnia Eka Putri; Aditiya Nugraha, Nurtama (Health Care : Journal of Community Service, 2024)
Background of this Community Service: Research in Sukoharjo City found that 76% of hypertension patients suffer from hypercholesterolemia, and there is a 23% higher risk of developing high cholesterol compared to normal cholesterol levels. Besides causing hypertension, hypercholesterolemia can also lead to coronary heart disease, and hypercholesterolemia in hypertension patients increases the risk of coronary heart disease. Objectives and Benefits: The purpose of this community service is to empower health workers and the community through acupressure training for hypercholesterolemia cases. Method: By providing education and training to health workers and the community in Desa Gonilan to prevent and manage hypercholesterolemia cases. This initiative will be conducted from February to August 2024. Results: The community can apply acupressure techniques to reduce cholesterol levels and enhance their immune system.